Skuteczne wspieranie Innego – rozważania nad uwarunkowaniami rozwoju zespołów terapeutycznych - Konieczna, Iwona; Smolińska, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
This paper will try to present developmental determinants multi specialist therapeutic teams which support people with disability (multi and trans disciplinary models of therapeutic teams). Developmental analysis of therapeutic teams will include formal, legal, organizational and theoretical aspects (basing on Kwiatkowski professional competences development theory).